Perdagangan Manusia Bermodus Pekerjaan Ilegal: Nasib Pekerja Migran Indonesia di Kamboja - Pangestu, Ragil; Riyanta, Stanislaus (LPPM Institut Pendidikan Nusantara Global, 2025)
Human trafficking through illegal employment remains a critical and underexplored issue in Southeast Asia, particularly affecting Indonesian Migrant Workers (PMI) in Cambodia. Despite numerous studies on labor exploitation, limited research has examined the comprehensive interplay between causes, modus operandi, impacts, and preventive measures specifically in the context of PMI working illegally abroad. This study addresses this gap by conducting a literature review focused on human trafficking through illegal employment, with emphasis on Indonesian migrant workers in Southeast Asia. The findings reveal that poverty, limited employment opportunities, low education, and lack of information on safe migration procedures are primary factors increasing PMI vulnerability. Syndicates exploit victims through unofficial recruitment, document falsification, identity confiscation, threats of violence, and forced labor. The consequences extend beyond the individual, causing physical and psychological trauma for victims, economic losses, reputational damage, and security risks for countries of origin. This study contributes by synthesizing previous findings and highlighting the need for integrated prevention strategies, including public education, economic empowerment, regulatory and law enforcement strengthening, and international cooperation. The results provide practical guidance for policymakers, government agencies, and NGOs to enhance oversight of illegal labor agencies and protect migrant workers more effectively. By clarifying the scope and mechanisms of illegal employment-based trafficking, this research offers both academic and practical insights to minimize human trafficking and improve the welfare of Indonesian migrant workers.